Attitudes towards ageing and their impact on health and wellbeing in later life: an agenda for further analysis. Issue 4 (12th December 2016) - Robertson, Guy
Abstract : Purpose: The purpose of this paper is to provide a high-level overview of a substantial body of research on the impact that negative attitudes towards ageing have on the health and wellbeing outcomes of people in later life and to highlight the need for a more interdisciplinary approach towards older people's wellbeing. Design/methodology/approach: The paper draws from an initial analysis of over 70 peers reviewed and published studies on the psychosocial impact of negative stereotypes about ageing. Findings: There is overwhelming evidence that the way in which people think about ageing can have a very significant adverse impact on a wide array of health and wellbeing outcomes. This research evidence is largely unknown, nor operationalised, within the field of health and social care policy or service development. Practical implications: The fact that beliefs and attitudes can have such a profound impact on health and wellbeing outcomes suggests the possibility of psychosocial interventions to address them in order to improve older people's experience of later life. There is a need for a much more interdisciplinary research agenda to take these findings forward. Social implications: The evidence suggests the need for a much more rigorous and comprehensive approach to addressing the effects of socially constructed ageist attitudes. Originality/value: Whilst the research itself is not new, the originality of this paper is its attempt to bring data from a different discipline into the health and social care ambit and thereby extend the knowledge base and create the possible conditions for the development and application of new psychosocial interventions to improve the lives of older people.